Exploring students’ perceptions of learning grammar in high school English learning - Kiki Octavianti Ginting; Safnidar Siahaan; Eka Wilany (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2026)
This study investigates senior high school students’ perceptions, challenges, and strategies in learning English grammar within the context of English as a Foreign Language (EFL). Using a qualitative descriptive design, data were collected through semi-structured interviews with twelve tenth-grade (Class X) students at one of the private senior high schools in Batam, Indonesia. The study aims to explore how students perceive grammar, identify the main difficulties they face, and examine their strategies to overcome those challenges. The findings reveal that most students perceive grammar as an essential foundation for constructing correct and meaningful sentences, yet they find it difficult to master due to its abstract nature and complex rules. The major challenges include confusion in tense usage, memorization of grammatical structures, and interference from the first language. External factors, such as teacher-centered instruction and limited classroom interaction, also contribute to students’ low motivation. Nevertheless, some students employ independent learning strategies, including watching English videos, practicing with peers, and using digital media to enhance their grammar skills. The study concludes that grammar instruction becomes more effective when integrated into communicative and interactive activities. These findings highlight the importance of designing engaging grammar lessons that promote both grammatical accuracy and communicative competence in EFL classrooms.